2011
DOI: 10.1002/smll.201101494
|View full text |Cite
|
Sign up to set email alerts
|

Protein‐Based Memristive Nanodevices

Abstract: A controllable and reproducible bipolar memristive protein nanodevice is fabricated by chemical immobilization of ferritin molecules within on‐wire lithography‐generated nanogaps. Control experiments suggest that programmable resistive switching is due to the electrochemical processes in the active centre of ferritin. Such ferritin‐based nanodevices with reversible resistance can be used for nonvolatile memory based on write‐read‐erase cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 55 publications
(77 reference statements)
2
77
0
Order By: Relevance
“…[ 2 ] Since memristors can achieve both high integration density and low switching power consumption thanks to high scalability down to only a few nanometers, they have been one of the most attractive devices for next-generation memory technology. [ 3 ] Various materials with switchable and retainable resistance have been used to realize the memristor memory, including proteins, [ 4,5 ] TiO 2 , [ 6 ] polyaniline, [ 7 ] Si, [ 8 ] MgO, [ 9,10 ] and VO 2 . [11][12][13][14] VO 2 is one of the most notable materials owing to its fast response time and large range of accessible resistance values through a metal-to-insulator transition (MIT).…”
mentioning
confidence: 99%
“…[ 2 ] Since memristors can achieve both high integration density and low switching power consumption thanks to high scalability down to only a few nanometers, they have been one of the most attractive devices for next-generation memory technology. [ 3 ] Various materials with switchable and retainable resistance have been used to realize the memristor memory, including proteins, [ 4,5 ] TiO 2 , [ 6 ] polyaniline, [ 7 ] Si, [ 8 ] MgO, [ 9,10 ] and VO 2 . [11][12][13][14] VO 2 is one of the most notable materials owing to its fast response time and large range of accessible resistance values through a metal-to-insulator transition (MIT).…”
mentioning
confidence: 99%
“…[151][152][153] Natural biomaterials, especially proteins, open up new opportunities for resistive-switching memory devices by endowing them with outstanding properties, such as mechanical fl exibility, biocompatibility, and light-weight, which renders them suitable for applications in biocompatible data-storage devices and biointegrated electronics. [ 32,[159][160][161][162][163][164] Silk protein exhibits more appealing properties compared with other biocompatible materials, such as ferritin, [ 159 ] cellulose, [ 165 ] and DNA, [ 166,167 ] for resistive-switching memory applications duo to its advantageous properties, such as mechanical robustness, fl exibility in thin-fi lm form, optical transparency, and compatibility with aqueous processing. [ 32,168 ] Silk-fi broin fi lms exhibited bipolar memristive switching behavior in a device with an indium tin oxide (ITO)/ fi broin/Al sandwich structure, with an OFF/ON ratio of 10 and retention time of 10 3 s. [ 78 ] The resistive switching of the above memristor was further studied at the microscopic scale, [ 169 ] which revealed that the current conduction process is dominated by fi lamentary conduction during LRS, and trap-assisted current conduction when in the HRS.…”
Section: Resistive-switching Memory Devicesmentioning
confidence: 99%
“…Finally, at sufficiently high voltage (region III), where the electrons fully occupy trap sites, an abrupt surge of current is observed, similar to the formation phenomena reported in numerous resistive switching devices. [4][5][6][7][11][12][13][14][31][32][33][34][36][37][38][39][40][41][42][43][44][45] In the present system, this abrupt turn-on is likely associated with a large local concentration of oxygen vacancies or to the development of a conducting metal (Zn) filaments with the a-ZnO layer. 33 To test the model, we have subjected HAT ZnO devices to different voltage pulse sequences.…”
Section: -mentioning
confidence: 99%